The Acceleration of Academic Supervision of Madrasa Principals in Improving the Quality of Learning - Herman, Herman; Jamin, Hanifuddin; Mahendra, Ichlasul (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to analyze the acceleration of academic supervision of madrasa principals in improving the quality of learning at several Madrasah Ibtidaiyah Negeri (MIN) Â in Aceh Jaya Regency. This study uses a qualitative approach with a phenomenological type in understanding the meaning behind the phenomenon of the acceleration of the madrasa principals academic supervision in the learning process. Methods of collecting data were carried out through observation, interviews, questionnaires and document studies. The data analysis technique uses data triangulation theory by utilizing data sources from document studies, observations, interviews and questionnaires related to the acceleration of the madrasa principal academic supervision and the quality of learning. The results showed that: 1) the form of the acceleration of the madrasa principal academic supervision at MIN in Aceh Jaya Regency was carried out individually and in groups. 2) the acceleration of academic supervision has not been carried out properly by the madrasa principals, starting from the planning stage of the academic supervision program to the stage of implementing academic supervision, and the stages of evaluating and following up on the results of supervision. 3) the quality of learning carried out by classroom teachers has been classified as good, this can be seen from the aspect of readiness and seriousness in preparing learning tools, implementing learning activities and evaluating / assessing learning activities. The implication of less optimal acceleration of academic supervision can result in less optimal quality of learning processes and outcomes. These findings can be recommended to the head of the Regency/City Ministry of Religious Affairs Office and madrasa supervisors to carry out programmatic guidance and training for madrasa principals on the implementation of academic supervision in madrasas.